Digital Technology Management in Learning and Academic Administration - Zhang Shuhao; Karta Sasmita; Muh. Takdir (Teunuleh Publisher, 2026)
Digital transformation in higher education necessitates the integration of technology into learning management and academic administration. Despite the widespread adoption of technology, its optimal use to enhance learning quality and the effectiveness of academic services remains inconsistent. This study seeks to analyze the use of digital technology in learning management and academic administration at China University of Petroleum (East China) and to identify the impacts and challenges encountered during its implementation. A mixed-methods approach with a case study design was employed. Data were collected from 120 respondents, including students, lecturers, and administrative staff, through questionnaires, interviews, observations, and documentation. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings reveal a high level of digital technology adoption, evidenced by the use of a learning management system (91.7%), virtual classrooms (85.0%), mobile applications (83.3%), and digital assessment systems (78.3%). Digital technology has been shown to improve learning accessibility, academic administrative efficiency, and student engagement. However, its application remains largely confined to course material delivery and does not fully support interactive learning. The novelty of this research lies in its integrated analysis of learning management and academic administration within the context of digital transformation in higher education. The study concludes that successful digital transformation relies not only on technology availability but also on the integration of pedagogy, enhancement of digital literacy, and strengthening of user competencies to support sustainable educational quality.